Beneficial Effect on Surrogate Markers of Heart Failure with Bisoprolol Up‐Titration to Recommended Targets in Korean Patients with Heart Failure and Left Ventricular Systolic Dysfunction. Issue 3 (June 2016) - Han, Seong Woo; Choi, Suk‐Won; Ryu, Kyu‐Hyung; Kim, Hyun‐Joong; Kim, Sung Hea; Shim, Wan Joo; Cha, Tae‐Joon; Choi, Dong‐Ju; Kim, Yong‐Jin; Yoo, Byung‐Su; Kim, Jun‐Hyung; Hwang, Kyung‐Kuk; et al.
Summary: Introduction: The objective of this study was to establish the benefit of bisoprolol up‐titration toward recommended dosage targets, versus lower‐dose maintenance, in heart failure (HF) patients with systolic dysfunction. Methods: Korean HF patients received bisoprolol 1.25 mg/day, incrementally up‐titrated toward 10 mg/day in the absence of contraindications. After 26 weeks' treatment, patients were grouped as low‐dose (<3.75 mg/day) or high‐dose (≥3.75 mg/day). Primary endpoint was change in serum N‐terminal probrain natriuretic peptide (NT‐proBNP). Other markers of HF were also evaluated. Results: 159 of 180 enrolled patients were evaluable. After 16 weeks' follow‐up, there were 52 and 107 patients in the low‐ and high‐dose groups respectively. Mean bisoprolol dosage was 5.4 mg/day; 24% of patients achieved target (10 mg/day). Mean logNT‐proBNP significantly decreased in both groups, with no significant difference in the magnitude of change between groups. Mean heart rate (HR) and blood pressure decreased significantly in both groups, but only HR showed a significantly greater change in high‐dose versus low‐dose patients. In both groups, mean left ventricular (LV) end‐systolic and end‐diastolic dimensions were significantly decreased and mean LV ejection fraction was significantly improved. Mean 6‐min walk test distances improved in both groups (significant in low‐dose patients only). Functional class improvement was observed in both low‐ and high‐dose patients. No patients were rehospitalized due to aggravated HF. Conclusions: In HF patients with systolic dysfunction, any bisoprolol dose is beneficial, but an attempt to up‐titrate toward guideline‐recommended dosages offers additional benefit in terms of restoration of LV systolic function and remodeling.